Morphological, Photosynthetic, and Physiological Responses of Rapeseed Leaf to Different Combinations of Red and Blue Lights at the Rosette Stage - Shengxin, Chang; Chunxia, Li; Xuyang, Yao; Song, Chen; Xuelei, Jiao; Xiaoying, Liu; Zhigang, Xu; Rongzhan, Guan (Frontiers in Plant Science, 2016)
Rapeseed (Brassica napus L.) is sensitive to light quality. The factory production of rapeseed seedlings for vegetable use and for transplanting in the field requires an investigation of the responses of rapeseed to light quality. This study evaluated the responses of the leaf of rapeseed (cv. ‘Zhongshuang 11’) to different ratios of red-photonflux (RPF) and blue-photonflux (BPF) from light emitting diodes (LEDs). The treatments were set as monochromatic lights, including 100R:0B% and 0R:100B%, and compound lights (CLs), including 75R:25B%, 50R:50B% and 25R:75B%. The total photonflux in all of the treatments was set as 550 μmolm-2s-1. With an increase of BPF, the rapeseed leaves changed from wrinkled blades and down-rolled margins to flat blades and slightly up-rolled margins, and the compact degree of palisade tissue increased. One layer of the cells of palisade tissue was present under 100R:0B%, whereas two layers were present under the other treatments. Compared to 100R:0B%, 0R:100B% enhanced the indexes of leaf thickness, leaf mass per area (LMA), stomatal density, chlorophyll (Chl) content per weight and photosynthetic capacity (Pmax), and the CLs with high BPF ratios enhanced these indexes. However, the 100R:0B% and CLs with high RPF ratios enhanced the net photosynthetic rate (Pn). The leaves under the CLs showed growth vigor, whereas the leaves under 100R:0B% or 0R:100B% were stressed with a low Fv/Fm (photosynthetic maximum quantum yield) and a high content of O2.- and H2O2. The top second leaves under 100R:0B% or 0R:100B% showed stress resistance responses with a high activity of antioxidase, but the top third leaves showed irreversible damage and inactivity of antioxidase. Our results showed that the rapeseed leaves grown under 0R:100B% or CLs with a high BPF ratio showed higher ability to utilize high photonflux, while the leaves grown under 100R:0B% or CLs with a low BPF ratio showed higher efficiency in utilizing low photonflux. Under different R:B photonflux ratios, red and blue lights may play mutual roles in Pn. When the blue light dominated, the Pn showed a B-preference. When the red light dominated, the Pn showed an R-preference. Furthermore, CLs were suitable for the Pn of rapeseed seedlings.